Development of a Robotic Arm Trainer with Color Detection Capabilities for Vocational Schools - Ummiati Rahmah; Mahmud Mustapa; Ririn Novita Sari; Mandeine Resyi (Ceddi Journal of Education, 2024)
This study aims to: (1) Analyze the learning conditions of the Robotic System Controller subject at SMK Negeri 4 Soppeng, (2) develop an ARM robotic color detector trainer for use in the Robotic System Controller practicum, (3) evaluate the validity of the trainer as a learning medium, and (4) Assess its practicality in the practicum. The development process followed the Computer-Assisted Instruction (CAI) model. The research subjects consisted of students majoring in Industrial Electronics at Vocational High School (SMKN) 4 Soppeng. Data were collected through validation sheets completed by media experts and response sheets filled out by students. The results showed that the media received a total average score of 93.5% from two media experts, categorizing it as very valid. Additionally, student trials yielded a total average score of 91%, placing it in the very practical category. These findings indicate that the ARM robotic color detector trainer is highly suitable and practical for use as a learning medium for students.